Inventory of Wild Orchids in Kuri Hill Ketapang West Kalimantan - Windy, Sylvia; Gusmalawati, Dwi; Zakiah, Zulfa (LenteraBio : Berkala Ilmiah Biologi, 2024)
Forest orchids are orchids that grow wild in forest areas. Orchids are unique in the form of beautiful labellum with various colours and shapes. Records of wild orchid species growing in the forests of West Kalimantan are still limited. This study aims to determine the species of orchids in hill Kuri, Ketapang Regency, West Kalimantan. The research was conducted using the cruising method. Morphological characters both qualitative and quantitative were observed and analysed descriptively. Fifteen species of orchids in Bukit Kuri were identified, namely Anoectochilus reinwardtii, Aphyllorchis maliauensis, Bulbophyllum anceps, Bulbophyllum sp1., Bulbophyllum sp2., Bulbophyllum sp3., Callostylis pulchella, Cylindrolobus sp., Dendrobium crumenatum, Dendrobium crumenatum, Flickingeria sp., Liparis elegans, Micropera fuscolutea, Plocoglottis lowii, Spathoglottis aurea, and Thrixspermum centipeda. Based on their mode of growth, the orchids found in Bukit Kuri consist of one terrestrial orchid, five lithophytic orchids, and nine epiphytic orchids. One of the 15 orchid species found was a new record for West Kalimantan, Indonesia, namely Aphyllorchis maliauensis.